PERAN MEDIA SOSIAL DALAM MEMPROMOSIKAN DESTINASI WISATA - Muhammad Faizal & Maskarto Lucky Nara Rosmadi (Master of Public Administration, Universitas Slamet Riyadi, 2018)
Tourism is one of the main assets that must develop as a capitaldevelopment in Bandung regency. One of the attractions that are in greatdemand by the tourists is Love Garden located in Soreang. The purpose ofthis research is to know the development of love garden attractions as wellas the role of social media to promote it. The research method used isdescriptive analytical with qualitative approach. Data collectiontechniques consist of primary data obtained from respondents andsecondary data in the form of literature, scientific journals both nationallyand internationally. From the research results obtained garden love is aprivate property that began to be developed in 2016. In promoting thepark the manager is very dependent on social media to promote the objectof tourism. nevertheless support from the local government, especially theDepartment of Tourism and Culture Bandung regency less optimal andlimited capital owned by the manager.Keywords: Village Tourism, Social Media, Promotion.